Association of Fatigue, Quality of Life and Functional Capacity in Breast Cancer Patients Receiving Adjuvant Chemotherapy - Amarsheda, Shila B.; Bhise, Anjali R (Asian Pacific Journal of Cancer Care, 2021)
Objectives: Cancer treatment related fatigue is a common and distressing symptom among breast cancer patients. With a greater longevity promote by advances in therapeutics & early diagnosis, interest has shifted to the assessment of quality of life (QOL). The concept of functional capacity has been used extensively in disability and rehabilitation research as an indicator of an individual’s ability to engage in physical activity. The aim of this study was to find the association of fatigue, QOL and functional capacity in post-operative breast cancer patients receiving adjuvant therapy. Materials and Methods: A total 30 participants who were receiving third cycle of chemotherapy were recruited from the Cancer Hospital. Facet fatigue questionnaire, FACT B questionnaire and 6-minute walk test (6MWT) were used for the assessment purpose of fatigue, QOL and functional capacity, respectively. Results: The Spearman’s correlation confirmed that the fatigue is strongly associated with subscale score of Fact B and very strongly associated with total score of fact B, Fact G and TOI. There was moderate association between the fatigue and functional capacity. There were above average values in total and subscale scores of QOL but among all the subscale scores of QOL, breast cancer subscale score was having lower value compared to others and social well being score was higher. Conclusion: Fatigue is having strong association with quality of life and moderate effect with functional capacity in these patients. Specific breast cancer related health is having more association among other quality of life aspects and social well being is least affected.